ICSID convention, regulations and rules (International Centre for Settlement of Investment Disputes WashingtonUS, 2003)
Indicates the facilities that ICSID provides for conciliation and arbitration of investment disputes between Contracting States and nationals of other Contracting States. Provides the ICSID regulations and rules which comprise administrative and financial regulations; Rules of procedure for the Institution of Conciliation and Arbitration Proceedings; Rules of Procedure for Conciliation Proceedings; and Rules of Procedure for Arbitration Proceedings.
Keywords: DISPUTE SETTLEMENT